2000
DOI: 10.1097/00007632-200008150-00008
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Findings in Patients With Persistent Sacroiliac Pain after Posterior Iliac Graft Harvesting

Abstract: There is a high prevalence of inner table disruption in patients with persistent sacroiliac joint pain after posterior iliac bone graft harvesting. The computed tomographic scan showed that involvement of the synovial part caused more severe degenerative changes than involvement of the ligamentous part.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 16 publications
0
52
0
1
Order By: Relevance
“…The first reported cases were of pelvic instability linked to damage to the posterosuperior sacroiliac ligaments, resulting from removal of iliac bone grafts from the posterior iliac crest [3][4][5][6][7][8][9][10][11]. This complication seems to be very rare [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first reported cases were of pelvic instability linked to damage to the posterosuperior sacroiliac ligaments, resulting from removal of iliac bone grafts from the posterior iliac crest [3][4][5][6][7][8][9][10][11]. This complication seems to be very rare [10].…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, attention was focused on the frequency of the donor site pain, concerning up to 30% of patients for Heary et al [9]. Not only could this syndrome be misdiagnosed as a sacroiliac syndrome because of the pain distribution, but, according to a recent study, the pain could arise from the sacroiliac joint itself [4]. Actually, the iliac-crest…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After discounting the SIJ as the etiologic source of pain based on a lack of objective findings on physical examination and imaging studies, Frymoyer et al [12] concluded that sacral sulcus pain encountered in 37 % of patients with low back pain after lumbar fusion was related to the iliac graft donor site. Ebraheim et al [13] studied patients with donor site pain and found a high frequency of a sacroiliac inner table disruption that resulted in accelerated degeneration of the joint and sacroiliac pain. In addition, Ha et al [27] reported that the SIJ on the side from which cancellous bone was harvested developed degeneration more often than on the normal side, although damage to the SIJ was not evident on computed tomography (CT) scans.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Cases of recurrent low back pain and/or lower extremity pain after lumbar/lumbosacral surgery are referred to as failed back surgery syndrome [5][6][7][8][9][10][11]. Several authors have suggested that the sacroiliac joint (SIJ) may be a possible source of persistent pain [4,12,13].…”
Section: Introductionmentioning
confidence: 99%